Fine needle aspiration cytology evaluation for classifying breast cancer using artificial neural network - Nor Ashidi, Mat Isa; Esugasini, Subramaniam; Mohd Yusoff, Mashor; Nor Hayati, Othman (Science Publications, 2009)
Link to publisher's homepage at http://scipub.org/scipub/index.php